Technological Gap in Adoption of Pulse Crop Production - Mahesh Pal , R. P. Singh; Mamta Singh (Indian Journal of Extension Education, 2014)
The technological gap between existing and recommended technologies of pulse crops was studied during 2011-12 among 50 respondents through Krishi Vigyan Kendra, Sant Kabir Nagar, Uttar Pradesh. It was found that a majority (56 %) of the farmers belonged to low technological gap category followed by medium (36 %) and high technological gap (8 %) in the use of high yielding varieties (HYVs) of pulse crops. In case of seed rate, 60, 28 and 12 per cent of the farmers belonged to low, medium and high technological gaps, respectively. In respect of seed treatment, a large proportion of farmers (44 %) were found in high technological gap category and 46 per cent farmers had high technological gap in method of sowing followed by medium (28 %) and low technological gap (26 %). The respondents were facing constraints in terms of unavailability of quality seeds in time, high cost of seeds, heavy weed infestation, high incidence of diseases and pests. Under socio-economic constraints, high cost of labour, high cost of inputs, unavailability of skilled labour in time, lack of support price and lack of subsidy for inputs were expressed as constraints by 78, 70, 62, 52 and 44 per cent of the respondents, respectively. Under technological constraints 66.00 per cent respondents also faced difficulties regarding weak extension support, lack of conviction and awareness about technologies.